The People, not the movement : opposition to CAFTA in Costa Rica, 2002-2007 - Frajman, Eduardo (2012)
Presents a thorough account of the origins, development, and main characteristics of the Costa Rican popular movement against the Central American Free Trade Agreement (CAFTA).